Problematik Pemberian Status Justice Collaborator pada Pelaku Tindak Pidana Korupsi - Bonar Yudhistira; Yasmirah Mandasari Saragih; Fauzan Fauzan; Yulia Christy Shintara Aruan; Erwin Efendi Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Granting Justice Collaborator (JC) status to perpetrators of criminal acts of corruption is one of the law enforcement strategies aimed at uncovering a wider network of corruption crimes. However, its implementation raises various problems, both in terms of law, morals and justice. This research aims to analyze the regulations underlying the granting of JC status, the criteria for its application, and the challenges that arise in practice. This study uses a juridical-normative method with an analytical approach to statutory regulations, court decisions and legal literature. The research results show that the granting of JC status is often no transparent, giving rise to controversy regarding the integrity of its implementation. Apart from that, there is a discrepancy between the ideal JC criteria as regulated in the Supreme Court Circular Letter (SEMA) Number 4 of 2011 and the practice of granting JC status. This has an impact on public trust in the criminal justice system. For this reason, it is necessary to strengthen regulations and tighter supervision so that granting JC status is in accordance with the principles of justice, transparency and accountability.